Postpartum Hemorrhage in Labor: Analyzing Risk Factors Across Demographic Groups - Sulastri, Sulastri; Suryani, Lilis; Muhede, Rohaya; Manaf, Salmiani Abdul; Irnawati, Irnawati; Seriana, Irma; Yuniwati, Cut; Sriyanti, Cut (Heca Sentra Analitika, 2025)
Postpartum hemorrhage (PPH) is a critical obstetric emergency and a major contributor to maternal mortality. Understanding risk factors across demographic groups is essential for guiding clinical surveillance. This study aimed to analyze the association between demographic and clinical factors, including maternal hemoglobin level, age, parity, weight, neonatal birth weight, and clinical causes of PPH based on the 4T framework (Tone, Tissue, Trauma, Thrombin), and the incidence of PPH among postpartum women. An observational cross-sectional study was conducted on 40 postpartum women who delivered vaginally at a Midwife Independent Practice (PMB) in Banda Aceh, Indonesia, between February and September 2021. Total sampling was applied. Data were collected through direct observation and clinical records. PPH was defined as estimated blood loss ≥500 mL within two hours after delivery. Statistical analysis included chi-square tests and odds ratio (OR) calculations. The prevalence of PPH in this sample was 42.5%. Perineal rupture was the most common clinical finding (77.5%), followed by retained placenta (12.5%) and uterine atony (10%). A significant association was found between clinical causes and the incidence of PPH (p = 0.001). Maternal anemia (Hb <12 g/dL) was significantly associated with PPH (p = 0.018; OR = 7.5), indicating a high-risk subgroup. Other demographic factors, age, parity, maternal weight, and neonatal birth weight were not significantly associated with PPH (p > 0.05). PPH was significantly associated with clinical causes, particularly uterine atony and retained placenta, as well as maternal anemia. These findings support the need for routine antenatal hemoglobin screening and strengthened postpartum monitoring in midwife-led clinical settings to improve early detection and response to bleeding risks.